Self-care practice of ostomy patients: contributions of the Orem's theory - Luciana Catunda Gomes Menezes; Maria Vilani Cavalcante Guedes; Roberta Meneses Oliveira; Shérida Karanini Paz de Oliveira; Lídia Stella Teixeira de Meneses; Maria Euridéa de Castro (Universidade Federal do Ceará, 2013)
This study aimed to identify the conditioning factors to self-care practice of ostomy patients, and verify knowledge and practices on stoma care. Descriptive and qualitative study, referencing the Orem's Self-Care Theory, carried out at the Ostomy Association of Fortaleza-CE, Brazil, in June and July 2007. We identified as the main conditioning factors for self-care: male, aged over 51 years, low education, from the capital city/metropolitan area, married, and with low family income. From the participants' statements, emerged three categories: Learning to take care of stoma: education-support system; Stoma Care: knowledge and practices; and Difficulties found in the practice of self-care. It was concluded that ostomy patients require a multidimensional and individualized nursing care, which enables them to perform self-care effectively.